Effect of Doping on the Photoelectric Properties of Borophene. (1st July 2021) - Zhang, Chunhong; Zhang, Zhongzheng; Yan, Wanjun; Qin, Xinmao
Abstract : Borophene is a new type of two-dimensional material with a series of unique and diversified properties. However, most of the research is still in its infancy and has not been studied in depth. Especially in the field of semiconductor optoelectronics, there is no related research on the modulation of photoelectric properties of borophene. In this work, we focus on the effect of doping on the photoelectric properties of borophene by using the first-principles pseudopotential plane wave method. We calculate the geometric structure, electronic structure, Mulliken population analysis, and optical properties of impurity ( X = Al, Ga) doped α -sheet borophene. The results show that α -sheet borophene is an indirect band gap semiconductor with 1.396 eV. The band gap becomes wider after Al and Ga doping, and the band gap values are 1.437 eV and 1.422 eV, respectively. Due to the orbital hybridization between a small number of Al-3p electrons and Ga-4p state electrons and a large number of B 2p state electrons near the Fermi level, the band gap of borophene changes and the peak value of the electron density of states reduces after doping. Mulliken population analysis shows that the B0 -B bond is mainly covalent bond, but there is also a small amount of ionic bond. However, when the impurity X is doped, the charge transfer between X and B atoms increases significantly, and the population of the corresponding X-B bonds decreases, indicating that the covalent bond strength of the chemical bonds in the doped system is weakened, and the chemical bonds have significant directionality. The calculation of optical properties shows that the static dielectric constant of the borophene material increases, and the appearance of a new dielectric peak indicates that the doping of Al and Ga can enhance the ability of borophene to store electromagnetic energy. After doping, the peak reflectivity decreases and the static refractive index n 0 increases, which also fills the gap in the absorption of red light and infrared light by borophene materials. The research results provide a basis for the development of borophene materials in the field of infrared detection devices. The above results indicate that doping can modulate the photoelectric properties of α -sheet borophene.